Strategi pemasaran produk dan jasa yang menarik di tingkat sekolah dasar - Fitri, Ana Zuyyina; Rahmawati, Iin Nur Indah; Damayanti, Setia (Maliki Interdisciplinary Journal, 2024)
Educational institutions that are able to survive and win the competition for educational products and services are institutions that can offer reputation, prospects, good quality education and bright opportunities for students to make the choices they want. Marketing of educational services is the activity of educational institutions that provide services or deliver educational services to consumers in a satisfactory manner. There are three types of marketing strategies that are attractive at the elementary school level, namely: differentiation, cost leadership and focus.